2015
DOI: 10.2169/internalmedicine.54.3506
|View full text |Cite
|
Sign up to set email alerts
|

Dysgeusia in a Patient with Guillain-Barré Syndrome Associated with Acute Hepatitis E: A Case Report and Literature Review

Abstract: Guillain-Barré syndrome (GBS) is usually triggered by viral or bacterial infection. In addition, it was recently reported that infection with hepatitis E virus (HEV) also causes GBS. A 49-year-old man presented with acute-onset paralysis in all extremities and dysgeusia during an episode of acute hepatitis. Serological tests showed the presence of anti-HEV IgM antibodies and HEV-RNA in the serum. As an electrophysiological examination showed acute demyelinating polyradiculoneuropathy, the patient was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
(64 reference statements)
2
4
0
Order By: Relevance
“…According to recent reports, HEV infection appears to be strongly associated with acute pancreatitis, neurological disorders (most commonly manifested as Guillain–Barré syndrome), hemolytic anemia as a result of glucose phosphate dehydrogenase deficiency, severe thrombocytopenia, glomerulonephritis and mixed cryoglobulinemia . In Japan, Guillain–Barré syndrome and peripheral facial palsy have been reported as extrahepatic manifestations related to HEV infection . In our present study, severe thrombocytopenia occurred in one (3 %) of 30 cases with AH‐E.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…According to recent reports, HEV infection appears to be strongly associated with acute pancreatitis, neurological disorders (most commonly manifested as Guillain–Barré syndrome), hemolytic anemia as a result of glucose phosphate dehydrogenase deficiency, severe thrombocytopenia, glomerulonephritis and mixed cryoglobulinemia . In Japan, Guillain–Barré syndrome and peripheral facial palsy have been reported as extrahepatic manifestations related to HEV infection . In our present study, severe thrombocytopenia occurred in one (3 %) of 30 cases with AH‐E.…”
Section: Discussionsupporting
confidence: 61%
“…12 In Japan, Guillain-Barré syndrome and peripheral facial palsy have been reported as extrahepatic manifestations related to HEV infection. 27,28 In our present study, severe thrombocytopenia occurred in one (3 %) of 30 cases with AH-E.…”
Section: Discussionsupporting
confidence: 51%
“…Among the neuro-muscular manifestations, the commonly reported were neuralgic amyotrophy (n = 102/179; 56.98%) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and Guillain-Barré syndrome (n = 36/179; 20.11%) [10,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The other rarer neurological manifestations that were reported include mononeuritis multiplex [10], encephalitis [11,13,39,41], cerebral ischemia [11,39], myasthenia gravis [42], polyneuromyopathy [24,43], meningo-radiculitis [10,44], epilepsy [11], encephalopathy [45], facial nerve palsy…”
Section: Neurological and Musculoskeletal Manifestationsmentioning
confidence: 99%
“…10,11 An association between infection with hepatitis E virus (HEV) and GBS has been suspected in several case reports and retrospective cohort studies of patients with HEV infection. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In 2013, a prospective case-control study reported positive IgM antibodies against HEV in 11% of patients with GBS in Bangladesh. 30 A second case-control study identified an associated acute HEV infection in 5% of patients with GBS in the Netherlands.…”
mentioning
confidence: 99%